2021
DOI: 10.1136/bmjopen-2020-043470
|View full text |Cite
|
Sign up to set email alerts
|

Rural family physician perspectives on communication with urban specialists: a qualitative study

Abstract: ObjectiveCommunication is a key competency for medical education and comprehensive patient care. In rural environments, communication between rural family physicians and urban specialists is an essential pathway for clinical decision making. The aim of this study was to explore rural physicians’ perspectives on communication with urban specialists during consultations and referrals.SettingNewfoundland and Labrador, Canada.ParticipantsThis qualitative study involved semistructured, one-on-one interviews with ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Last, there is acknowledgment of context as an important factor, with rural settings having unique features and characteristics in multiple ways compared to urban settings. 16 - 18 What this research adds is the multi-participant perspective within 1 study illuminating how values on the practitioner side may be reflected (or not) in the patient’s perspective. Also, this research shows how the different roles in the practice support and complement one another with their values, but how they may be executed differently.…”
Section: Discussionmentioning
confidence: 99%
“…Last, there is acknowledgment of context as an important factor, with rural settings having unique features and characteristics in multiple ways compared to urban settings. 16 - 18 What this research adds is the multi-participant perspective within 1 study illuminating how values on the practitioner side may be reflected (or not) in the patient’s perspective. Also, this research shows how the different roles in the practice support and complement one another with their values, but how they may be executed differently.…”
Section: Discussionmentioning
confidence: 99%
“…These specialists are the ones who receive a rural physician’s referred patients, provide advice by phone during emergencies and extend emotional support to rural physicians in low-resourced centres in times of great stress. Therefore, when an urban specialist has a pleasant demeanour, understands the conditions under which rural physicians work, and respects a rural physician’s clinical and social knowledge about their patients, it facilitates open communication, boosts confidence, and augments a sense of advocacy in rural physicians towards their community and patients [ 15 ].…”
Section: Textmentioning
confidence: 99%
“…Although SCT has not been used as part of healthcare personnel's elderly communication training, it has been used as a lens to conceptualize how health personnel communicates with each other. In a study that examined communication between urban and rural physicians during consultations [5], it was found that both groups of physicians perceived that they experienced challenges in understanding each other's contexts (e.g., depth of familiarity with a patient). The language and jargon used (i.e., speech codes) were the main reasons for suboptimal communication patterns that often led to suboptimal patient outcomes.…”
Section: Proposed Solutionmentioning
confidence: 99%